A new species of the genus Parapentacentrus Shiraki, 1930 from Yunnan, China (Orthoptera: Gryllidae: Itarinae) - Liu, Yi-Jiao; He, Zhu-Qing (Zootaxa, 2021)
The genus Parapentacentrus Shiraki, 1930 includes two species with long wings. In this paper, we report one new species, P. brevipennis He sp. nov., from Jinping, Yunnan, China. The new species have short forewings and hindwings, and have differences in the shape of supra-anal plate and male genitalia. DNA Barcode (COI gene) of this new species are provided. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).